Philosophical Studies in The Development of Basic Writing Materials Based on Brain Based Learning - Mu'thia Mubasyira; Aceng Rahmat; Saifur Rohman (Jurnal Studi Guru dan Pembelajaran, 2021)
This research was conducted to analyze philosophical studies contained in the development of basic writing materials based on brain based learning. Philosophical studies are used there are three, namely, ontology, epistimology and axiology. This research is qualitative research that uses descriptive methods. Data collection techniques used using library studies against references related to the topics studied in this article in the form of literature related to the development of teaching materials, basic writing and brain based learning. The results of this study are a discussion of three studies of the philosophy of science on the development of basic writing materials based on brain based learning. The results of this study are a discussion of three studies of the philosophy of science on the development of basic writing materials based on brain based learning. Ontology studies are formulated to examine a development of teaching materials in third semester students who take basic writing courses in the English education study program, Universitas Indraprasta PGRI. Epistimologically, the methods used in the study are in accordance with learning models based on brain abilities developed by Jensen. Then the axiology foundation contained in the research is the value of educational technology and human value because basically this research is done to develop educational technology in the form of brain based learning teaching materials that can support the performance of lecturers and students so that the learning outcomes created can be maximized